Exploring the Changes in Teaching Strategies Enabled by Information and Communication Technology (International Journal of Theory and Application in Elementary and Secondary School Education, 2019)
The Information and Communication Technology (ICT) in now a day plays a very strategic role in the transforming phase of education. Thus government also taking many initiatives and tried to integrate ICT to teaching learning process like the introduction of ICT@School Scheme. But the problem lies in its effective use in classroom. Is teacher being competent enough in use of ICT in classroom, what are the some of the changes teachers are making when they used ICT tools with their students in the classroom and how strategies are changing, what contributes to the change, and what is the change in classroom dynamics and traditional time structures? These were the few issues which addressed in the present study. For this purpose, a qualitative approach with an interview study was adopted for the study. Further, it delimited to Cuttack district of Odisha and ten secondary schools and total thirty teachers, three from each school was selected as its sample by using purposive sampling method. The investigator makes classroom observation, extensive field notes and interview with the respondents for collection of data. The collected data was analyzed by thematic description related to foregoing issues with specific reference to the four key themes: the changing role of the teacher, classroom dynamics, teacher predictions of ICT in school and the concept of the classroom. The findings of the study revealed that the ICT in the classroom influenced the process of learning and in order to integrate ICT effectively, teachers are adopting different teaching strategies. Further it has also been revealed that they need drill for the power shift in the classroom because often students had more knowledge of ICT than them. The findings also revealed that the dynamic of the classroom was also changing due to ICT. Finally, the teachers needed time to learn about the technology and to understand how to integrate ICT into the curriculum.